A new dinosaur tracksite with small footprints in the Urbión Group (Cameros Basin, Lower Cretaceous, La Rioja, Spain) - Díaz Martínez, Ignacio (2014)
Fil: Díaz Martínez, Ignacio. Universidad de La Rioja; España.